An Unusual Laryngeal Injury - A Kohli; P Bhadoria; A Bhalotra; R Anand; P Goyal (Indian Journal of Anaesthesia, 2007)
Blunt injuries to the anterior neck are most commonly due to road traffic accidents but the incidence of such types of injuries are decreasing probably due to stricter laws pertaining to seat belts and drunken driving. Experience in managing such injuries is limited due to their rarity. The mainstay of management revolves around establishing and maintaining a patent airway and integrity of the spine. Here we document a case of a 25 year old male who met with a Road traffic accident while driving a motorbike and sustained a clear cut linear wound on the right side of the neck with minimal airleak due to the helmet clip. On exploration, he was found to have massive epiglottic edema, mucosal abrasions, lacerations and a thyroid cartilage fracture. The mechanism of injury was probably a combination of penetrating and blunt trauma neck. This case highlights the mechanism of laryngeal injury, its presentation and management